2009
DOI: 10.1080/00016340902777517
|View full text |Cite
|
Sign up to set email alerts
|

The novel ischemia marker ‘ischemia‐modified albumin’ is increased in normal pregnancies

Abstract: The aim of this prospective case-control study was to determine the change in serum maternal ischemia-modified albumin (IMA) during normal pregnancies. A total of 117 pregnant (first trimester (n=24), second trimester (n=34), and third trimester (n=35)) and non-pregnant healthy women (n=23) were included. Maternal serum IMA, Malondialdehyde (MDA), and albumin levels were measured. Compared with non-pregnant women, the cross-sectional mean IMA levels in pregnant women were significantly increased, while the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 13 publications
3
20
0
2
Order By: Relevance
“…There were also many reports showing its relationship with various ischemia‐related conditions, such as acute coronary syndrome . Recently, in two studies among normal pregnancies, it has been demonstrated that maternal serum IMA levels increased to supra‐physiological levels in the first trimester of pregnancy compared to non‐pregnant controls, and these levels continued to rise from the first trimester to the third trimester . In previous reports, it has been clearly demonstrated that pre‐eclampsia is a disease associated with placental hypoxia and increased oxidative stress occurring concurrently with ischemia .…”
Section: Discussionmentioning
confidence: 97%
“…There were also many reports showing its relationship with various ischemia‐related conditions, such as acute coronary syndrome . Recently, in two studies among normal pregnancies, it has been demonstrated that maternal serum IMA levels increased to supra‐physiological levels in the first trimester of pregnancy compared to non‐pregnant controls, and these levels continued to rise from the first trimester to the third trimester . In previous reports, it has been clearly demonstrated that pre‐eclampsia is a disease associated with placental hypoxia and increased oxidative stress occurring concurrently with ischemia .…”
Section: Discussionmentioning
confidence: 97%
“…Also, ischemia-modified albumin is a new biomarker, and serum IMA levels are also affected by various physiologic changes that cause oxidative stress, such as pregnancy; many comorbid conditions such as malignancy, chronic liver failure, end-stage renal failure, cerebral ischemia, and acute infections have also led to false-positive IMA results. [20][21][22][23] We were not able to control all of the variables that could possibly influence IMA levels. Patients with mesenteric ischemia are usually of advanced age and have comorbid diseases, which reduce the specificity and positive predictive value of the test.…”
Section: Limitationsmentioning
confidence: 99%
“…IMA levels are mostly more elevated than the concentration detected during myocardial ischemia in women whose pregnancy has just started (Prefumo et al, 2007, Guven et al, 2009, Van Rijn et al, 2008. Moreover, IMA levels become higher in complicated pregnancies than regular ones (Dogan et al, 2015, Karadeniz et al, 2015, Cengiz et al, 2015.…”
Section: Introductionmentioning
confidence: 89%
“…Recent studies show that serum IMA levels are physiologically elevated during normal pregnancies in humans, and that maternal IMA levels are lower than the cutoff which was applied in detecting cardiac ischemia (Prefomu et al, 2007, Guven et al, 2009, Van Rijn et al, 2008.…”
Section: Güvenmentioning
confidence: 99%
See 1 more Smart Citation